Question

This question has multiple correct options

Verified by Toppr

Correct option is

$(R−h)_{2}+r_{2}=R_{2}$

$R_{2}+h_{2}−2Rh+r_{2}=R_{2}$

$h_{2}+r_{2}=2Rh$

$2hh_{2}+r_{2} =R$ ___(i)

$r>>>h$

$R=2hr_{2} $

$∵h=2gw_{2}r_{2} $

$R=2w_{2}r_{2}r_{2}2g $

$R=w_{2}g $ ___(ii)

$Vμ_{1} −uμ_{2} =Rμ_{1}−μ_{2} $

$V1 +3u4 =R1−34 $

$V1 =−(3R1 +3(H−h)4 )$

$V1 =−[3R1 +3H4 ]$

Put the value of equation (ii) $h<<H$

$V1 =−[3H4 [1+43H 39w_{2} ]]$

$V=−[43H (1+4w_{2}H )_{−1}]$

Solve any question of Laws of Motion with:-

0

0